Human bioaccessibility and absorption by intestinal cells of potentially harmful elements from urban environmental matrices - Boim, Alexys Giorgia Friol (2018)
Potentially harmful elements (PHE) are found naturally in soils, usually in low concentrations. However, due to the intensity of the anthropic activities, the concentrations of these elements may increase and have negative effects on the environment and human health. Methods for risk assessment may predict or indicate the level of exposure to contamination of an area. In addition to the total or pseudo-total concentration of PHE, generally extracted with acidic solutions, it is possible to determine the reactive, bioavailable and bioaccessible levels of these elements in order to evaluate the degree of soil contamination. Urban soil samples located in residential areas were collected in Piracicaba, State of São Paulo (SP) and in Santo Amaro, State of Bahia, including soils collected near a primary lead smelter area (COBRAC/Plumbum), where researchers detected elevated levels of PHE. Soils samples in an old lead metallurgy plant (Usina do Calabouço / IPT), which today belongs to the Centro Integrado de Ensino Multidisciplinar (CIEM/ Companhia de Pesquisa de Recursos Minerais (CPRM) - Geological Survey of Brazil) in Apiaí, located in the Upper Ribeira Valley (SP) were also collected. In vitro methods have been used in several countries to assess the bioaccessibility of PHE in humans. In this study, procedures based on ingestion and inhalation of soils using the Unified BARGE Method (UBM) and Artificial Lysosomal Fluid (ALF) methods were used to obtain the bioaccessible concentration in the gastrointestinal and pulmonary tract, respectively. As the bioaccessible fraction does not estimate the concentration absorbed and transported into the bloodstream, the in vitro method using Caco-2 cells, which are derived from human colon adenocarcinoma, was used to assess the amount of PHE that intestinal cells can absorb. The mineralogical data was obtained, and the sequential extraction of As, Cd, Cu, Mn, Pb and Zn was carried out to evaluate their interaction with lung fluid and gastric/gastrointestinal fluids. As expected, mine tailing samples had the highest pseudo-total concentrations of PHE in comparison to soil and sediment samples, both in the bulk soil (2 mm) and in the 250 μm and 10 μm sizes. Both respiratory and oral bioaccessibility of PHE varied widely among matrices, indicating that they were influenced by matrices´ chemistry, physical and mineralogical characteristics. The respiratory bioaccessible fraction, calculated as a percentage of the PHE pseudo-total concentrations, ranged from 13 - 109% for As; 14 - 98% for Cd; 21 - 89% for Cu; 46 - 140% for Pb, 35 - 88% for Mn and; 21 - 154% for Zn. Gastric bioaccessibility was greater than gastrointestinal bioaccessibility, ranging from 0-33% and 0-26% for As; 0-69% and 0-40% for Cd; 18-75% and 12-89% for Cu; 24-83% and 7-50% for Pb; 43-105% and 27-97% for Mn; 14-88% and 6-46% for Zn. Pseudo-total concentration provided a good estimate of respiratory and oral bioaccessibility, but the in-vitro methods provided more accurate results. Caco-2 cell line (in vitro test) was a good model for evaluating the effect of PHE exposure, but further studies on the transport and bioavailability of PHE in intestinal cells are needed.